2021
DOI: 10.1111/jne.13006
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y suppresses thermogenic and cardiovascular sympathetic nerve activity via Y1 receptors in the paraventricular nucleus and dorsomedial hypothalamus

Abstract: In hungry animals, neuropeptide Y (NPY) neurones in the arcuate nucleus (ArcN) are activated to suppress energy expenditure, in part by decreasing brown adipose tissue sympathetic nerve activity (BAT SNA); however, the NPY receptor subtype and brain neurocircuitry are unclear. In the present study, we investigated the inhibition of BAT SNA by exogenous and endogenous NPY via binding to Y1 receptors (NPY1R) in the hypothalamic paraventricular nucleus (PVN) and dorsomedial hypothalamus (DMH), in anaesthetised ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Chemokines and chemokine receptors have long been associated with obesity-linked inflammation and insulin resistance and modulation of the chemokine/Chemokine receptor axis is considered a novel approach for the treatment of obesity and associated metabolic disorders (31)(32). Similarly, previous studies have reported increased expression of NPYR1 expression in adipose tissue of obese human subjects and high-fat diet-fed mice (34)(35). Moreover, selective antagonism of pe-ripheral NPYR1 was shown to prevent insulin resistance and other metabolic abnormalities in high-fat diet-fed mice (36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines and chemokine receptors have long been associated with obesity-linked inflammation and insulin resistance and modulation of the chemokine/Chemokine receptor axis is considered a novel approach for the treatment of obesity and associated metabolic disorders (31)(32). Similarly, previous studies have reported increased expression of NPYR1 expression in adipose tissue of obese human subjects and high-fat diet-fed mice (34)(35). Moreover, selective antagonism of pe-ripheral NPYR1 was shown to prevent insulin resistance and other metabolic abnormalities in high-fat diet-fed mice (36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Many GPCRs in this list have previously been studied for their role in adipose biology. These include alpha-and beta-adrenergic receptors (11)(12)(13)(14)(15)(16), adenosine receptors (19), free fatty acid receptors (7,17,18), adhesion receptors (20,21), hydroxycarboxylic acid receptors (22,23), gastric inhibitory peptide (27)(28)(29), chemokine receptors (30)(31) and many others (32)(33)(34)(35). Interestingly, many GPCRs with notable expression profiles in adipose tissue and adipocytes have no known role in adipose metabolism.…”
Section: Gpcrs Of Interestmentioning
confidence: 99%
“…DMH is a heterogeneous nucleus containing orexin-expressing, glutamatergic, cholinergic [17], and GABAergic neurons, which can also be divided into many subtypes, such as galaninergic-expressing [23] and neuropeptide Y [35]. There are a large number of orexin neurons in the DMH [36], which also intensively project with the median preoptic nucleus and send projections to the ventrolateral preoptic nucleus, an important sleep regulation center [24], and the LH, the main arousal regulation center.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have been associated with feeding behavior, suggesting the Brs3-Adarb2 population to be involved in the control of feeding behavior. 35,[38][39][40][41][42] Interestingly, Mc4r, Brs3, Npy1r, and Vgf have also been associated with regulating energy expenditure through the sympathetic nervous system, 35,42,43 suggesting the Brs3-Adarb2 population to also be involved in sympathetic outflow. This indicates that at least part of the preautonomic neurons may also project centrally, which further highlights the difficulty in comprehensively classifying the central projections of the PVN.…”
Section: Preautonomic Neurons Are Embedded In the Adarb2 + Clustersmentioning
confidence: 99%